The Therapeutic Potential of Metformin for Metabolic Associated Fatty Liver Disease: Bioinformatics Analysis - Lin, Chen-Shi; Ma, Hong (Archives of Clinical and Medical Case Reports, 2024)
Metabolic associated fatty liver disease (MAFLD) is associated with obesity and metabolic dysfunctions, but its molecular mechanisms remain elusive and effective treatments are lacking. Metformin is a potential therapeutic agent for MAFLD due to its effects on insulin resistance and fat metabolism dysregulation. This study used bioinformatics analysis to identify differentially expressed genes (DEGs) in MAFLD and explore the potential targets of metformin treatment. We selected a MAFLD dataset from the Gene Expression Omnibus (GEO) database and screened 425 DEGs, including 278 up-regulated and 147 down-regulated genes. We also identified 183 genes related to metformin treatment using the Genclip3 database and found 13 common genes with the DEGs. The Genome Ontology (GO) enrichment analysis of these genes revealed biological processes such as suppression of inflammation and promotion of glycolipid metabolism, while the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways involved diabetic complications and inflammatory signaling. The protein-protein interaction (PPI) analysis identified IL1B, IL6, IL10 and CCL2 as the core proteins. Based on the PPI network, we selected the top 9 genes as hub genes, including IL6, IL1B, IL10, CCL2, FOXO1, PIGS2, IGFBP1, GCK, and MYC. The study suggests that metformin may target multiple pathways for the treatment of MAFLD, mainly involving anti-inflammation, regulation of glycolipid metabolism, and anti-hepatic fibrosis.